Waste Characteristics And Environmental Perceptions Among Lake Communities: A Case Study Of Plastics Waste Management In Yoboi Village, Lake Sentani - Titia Erika Sarlota Awom; Ardian Hangga Kelana; Saul weipsa; Yekson Soll (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Plastic waste has become a growing environmental challenge for lake communities, particularly in water-based settlements that depend on aquatic ecosystems for their livelihood and tourism activities. This research examines the characteristics of waste and environmental perceptions among the community of Yoboi Village, Lake Sentani, Jayapura Regency, Indonesia. Utilizing a qualitative case study approach, the research explores how plastic waste generated, managed, and perceived within the socio-ecological context of a water-based tourism village. Data were collected through non-participant observations, semi-structured interviews, and document analysis. The result shown that thin plastic packaging, plastic shopping bags, beverage bottles, and food packaging were the most commonly observed types of plastic waste in residential areas and along the lakeshore. Although community members generally demonstrated a good understanding of the environmental impacts of plastic waste, this awareness was not consistently reflected in everyday waste management practices. The persistence of plastic waste was influenced by daily consumption patterns, limited waste management infrastructures, established disposal habits, and the capacity of community institutions to organize collective waste management initiatives. In conclusion, plastic waste management in Yoboi Village should be understood as a socio-ecological issue requiring integrated, community-based strategies that combine environmental education, improved waste management services, and active local participation to protect the sustainability of the Lake Sentani ecosystem.